Pengaruh Ukuran Perusahaan, Profitabilitas, Leverage, Likuiditas dan Sales Growth terhadap Kebijakan Dividen (Studi Empiris pada Perusahaan LQ45 Yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2018) - Arifa Nur Azizah; Riana R Dewi; Purnama Siddi (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
This study aims to examine and analyze the effect of company size, profitability, leverage, liquidity and sales growth on dividend policy on LQ45 companies listed on the Indonesia Stock Exchange in 2016-2018. The population of this study is all companies belonging to the LQ45 index listed on the Indonesia Stock Exchange in 2016-2018. The use of samples in research using Purposive Sampling with certain criteria in order to obtain 66 data samples to be studied. The data used are secondary data sourced from financial statements. This research uses Multiple Linear Regression Analysis Test method. From these tests it can be seen that Company Size, Profitability and Leverage affect Dividend Policy. While Liquidity and Sales growth does not affect the Dividend Policy in LQ45 Companies in 2016-2018.